2023
DOI: 10.1111/jeu.12971
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic placement of the protosteloid amoeba Microglomus paxillus identifies another case of sporocarpic fruiting in Discosea (Amoebozoa)

Abstract: Protosteloid amoebae are a paraphyletic assemblage of amoeboid protists found exclusively in the eukaryotic assemblage Amoebozoa. These amoebae can facultatively form a dispersal structure known as a fruiting body, or more specifically, a sporocarp, from a single amoeboid cell. Sporocarps consist of one to a few spores atop a noncellular stalk. Protosteloid amoebae are known in two out of three well‐established major assemblages of Amoebozoa. Amoebae with a protosteloid life cycle are known in the major Amoebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
3
1
0
Order By: Relevance
“…Additionally, the topology of the tree, including the deep branches, matches previous phylogenomic analyses of Amoebozoa (Kang et al., 2017) to the exclusion of the Tevosa clade from Kang et al., 2017 previously demonstrated in Tice et al. (2023) and Tekle et al. (2022).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, the topology of the tree, including the deep branches, matches previous phylogenomic analyses of Amoebozoa (Kang et al., 2017) to the exclusion of the Tevosa clade from Kang et al., 2017 previously demonstrated in Tice et al. (2023) and Tekle et al. (2022).…”
Section: Resultssupporting
confidence: 82%
“…As in the SSU rRNA gene phylogenies, the phylogenomic analyses illustrate that our new isolates are paraphyletic of one another, with Union 16-1-3 and MSU2-1 grouping together. Additionally, the topology of the tree, including the deep branches, matches previous phylogenomic analyses of Amoebozoa (Kang et al, 2017) to the exclusion of the Tevosa clade from Kang et al, 2017 previously demonstrated in Tice et al (2023) and Tekle et al (2022). Rather in our analyses and these latter studies Evosea groups with Discosea.…”
Section: Phylogenomic Analysessupporting
confidence: 88%
“…In one [33], Rhizomastixidae forms a sister lineage to Pelomyxidae, but maximum-likelihood analysis of the same dataset preferred the alternative, in which Pelomyxidae and Mastigamoebidae are sisters. The latter was recovered in other studies [64, 65] and in our SSU rDNA phylogeny (Fig. S1), and will serve as the framework for our evolutionary inferences.…”
Section: Resultssupporting
confidence: 68%
“…The sampling captures different lifestyles and comprises representatives of all major Archamoebae lineages (Figs 1a and S1, available in the online version of this article). The placement of the Rhizomastixidae clade is conflicting in phylogenomic analyses [33,64,65]. In one [33], Rhizomastixidae forms a sister lineage to Pelomyxidae, but maximum-likelihood analysis of the same dataset preferred the alternative, in which Pelomyxidae and Mastigamoebidae are sisters.…”
Section: Species and Assembliesmentioning
confidence: 99%